The Establishment of the Inquisition in Brazil: An Aborted Project - Santos Pereira, Ana Margarida (2019)
The Inquisition of Lisbon extended its jurisdiction to the Portuguese territories of the Atlantic, including Brazil. Nonetheless, the religious authorities and the settlers themselves, or at least some, frequently requested the establishment of a court in Portuguese America. In this article, we will analyse the projects that were discussed in the 17th century, with a view to achieving that objective. Starting from the information contained in the inquisitorial documentation, we will try to show that Monarchy, Church and Inquisition had disparaging interests, and this was decisive so that none of the proposals under discussion came to be put into practice.